Divergent Effects Of Job Control On Coping With Work Stressors: The Key Role Of Self-Efficacy - Schaubroeck, John; Merritt, Deryl E. (Academy of Management Journal, 1997)
This study identifies job self-efficacy as a moderating variable that may determine whether job control contributes positively or negative to coping with work stressors. Data from two samples (health professionals and an occupationally diverse group) demonstrated similar interactions between demands, control, and self-efficacy predicting blood pressure. These results may reconcile the previous inconsistent and largely method-bound support for Karasek's job demands-control model and suggest that efforts to improve job self-efficacy may be as important to reducing the cardiovascular consequences of job stress as efforts to enhance control.